Principles of Engineering Economy. - Thomsen, C. Torben; Sterling, Robert R. (The Accounting Review, 1971)
Abstract Reviews the book "Principles of Engineering Economy," 5th ed., by Eugene L. Grant and W. Grant Ireson.